'Green' derivatization of carbon nanotubes with Nylon 6 and L-alanine - Basiuk, V; Salvador-Morales, C; Basiuk, E; Jacobs, R; Ward, M; Chu, B; Sim, R; Green, M (2006)
Amide derivatives of l-alanine and ε-caprolactam were readily obtained on diamine-functionalized oxidized single-walled and pristine multi-walled carbon nanotubes through a one-step direct amidation reaction, which employs thermal activation at 160-200 °C instead of chemical activation, avoids the use of organic solvents, and requires a few hours only for completion. In the case of ε-caprolactam, amino groups attached to the nanotubes initiated polymerization into Nylon 6. The functionalized nanotubes were characterized by infrared and Raman spectroscopy, scanning and transmission electron microscopy, atomic force microscopy, thermal gravimetric analysis and differential scanning calorimetry. This journal is © The Royal Society of Chemistry.